The characterization of adipose tissue in distinct anatomical regions of the Kazakh horse: a comprehensive analysis of the morphology, fatty acid profile, and lipidomic profile - Wang, Ran; Ren, Wanlu; Li, Luling; Li, Zexu; Ma, Shikun; Shan, Dehaxi; Huang, Qiuping; Su, Yi; Wang, Jianwen (Frontiers in Animal Science, 2025)
The Kazakh horse is one of the important horse breeds in China. The distribution of its adipose tissue and the characteristics of lipid metabolism play a crucial role in the horse’s fat utilization efficiency, meat quality, and energy storage. This study employed tissue sectioning, LC-MS/MS, and related methodologies to characterize variations in cellular morphology, fatty acid profiles, and lipid metabolite composition across neck adipose tissue (NAT), abdominal adipose tissue (AAT), and mesenteric adipose tissue (MAT) in Kazakh horses. Adipocyte area and diameter were largest in MAT, while Adipocyte number was highest in NAT. Notably, horse adipose tissue demonstrated a high abundance of unsaturated fatty acids, particularly oleic acid and linoleic acid. Among these, saturated fatty acids and polyunsaturated fatty acids were higher in MAT, while monounsaturated fatty acids were higher in NAT. Lipidomic profiling identified 170, 44, and 109 differentially abundant lipid species (DALs) in the NAT-MAT, AAT-MAT, and NAT-AAT comparisons, respectively. With triglycerides (TG), phosphatidylcholine (PC), and phosphatidylethanolamine (PE) being particularly prominent. KEGG results show that Glycerophospholipid metabolism, Glycerolipid metabolism, Linoleic acid metabolism, and alpha-Linolenic acid metabolism are the main pathways involved in adipose metabolism. These findings delineate regional disparities in adipose cellular morphology, fatty acid profiles, and lipid metabolite composition in the Kazakh horse, offering mechanistic insights to inform strategies for lipid regulation and tissue-specific fat management.